Philosophy as Anti-Religion in the Work of Alain Badiou - Clemens, Justin (Sophia, 2008)
The Heideggerian rupture in the history of philosophy in the name of a phenomenological and poetic ontology has provided an opening which many of the key figures in twentieth century continental thought have exploited. However, this opening was marked by Heidegger himself as an ambiguous one, insofar as metaphysics was perhaps integrally ‘onto-theology,’ that is, ultimately continuous with the world-historical capture of the thought of being. This piece argues that the philosophy of Alain Badiou, which departs from the recognition that Heidegger is the ‘last universally recognised philosopher’, provides the means for a radical reconsideration of the philosophy-theology relationship in its specifically Heideggerian form, involving as it does further questions of science and technology, the status of the poem, and the nature of ontological thought as such. We argue that, through the deployment of mathematics as ontology, the Gordian knot of onto-theology and its legion of consequences can be cut, and a new assemblage of many of the key Heideggerian motifs can be put into play: the poem, history, and philosophy itself.